One for all, all for one? Supposing the ECtHR’s position on COVID-19 vaccines - Béres, Nóra (The ECHR at 70: The Central European Narrative, 2025)
At the time of writing, COVID-19 no longer constitutes a public health emergency of international concern. However, the compatibility of coronavirus vaccines with the interests of the European Court of Human Rights (ECtHR) is still worth mentioning. In 2020 and 2021, while humanity struggled with the pandemic, the long list of fundamental rights dilemmas expanded – with the issue of human rights certainly generating the most relevant public resonance. Alongside curfews and less stringent restrictions on the freedom of movement was the compulsory vaccination against COVID-19. Therefore, the decision of the ECtHR in Vavřička et al. v. the Czech Republic could hardly be more timely in helping us to take stock of the conditions under which compulsory coronavirus vaccination may be compatible with humanrights law. Therefore, this paper seeks to provide a focused case analysis on the only decision of the court related to compulsory vaccines – and uses analogy to make conclusions on the compatibility of coronavirus vaccines with the European Convention on Human Rights (ECHR). Keywords: compulsory vaccination, COVID-19, ECHR, ECtHR, right to private life